1981
DOI: 10.1080/00913847.1981.11711208
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rapid Weight Loss on Physiological Functions in Wrestlers

Abstract: In brief: To assess the effects of rapid weight reduction, four university wrestlers decreased their body weight by 8% over a four-day period by food and liquid intake reductions. Significant decreases in muscle glycogen concentration and dynamic strength, but not aerobic or anaerobic capacity, accompanied weight loss. A three-hour rehydration period did not improve glycogen levels or strength performance. These results suggest that rapid weight reduction may impair wrestling performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
68
0
5

Year Published

1993
1993
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 9 publications
9
68
0
5
Order By: Relevance
“…Similar adverse effects of weight loss on the exercise heart rate of wrestlers during submaximal work have been confirmed by others (1,73). In contrast, cardiovascular function as indicated by peak oxygen uptake (peak V 0 3 during maximal work does not appear to be hampered (7,30), even when wrestlers reduce their body weight by as much as 8%. Others have found that peak VOz and endurance time for running on the treadmill were decreased (77); these changes could be caused by rapid weight loss-induced decreases in muscle glycogen, plasma volume, and impaired thermoregulation.…”
supporting
confidence: 63%
See 4 more Smart Citations
“…Similar adverse effects of weight loss on the exercise heart rate of wrestlers during submaximal work have been confirmed by others (1,73). In contrast, cardiovascular function as indicated by peak oxygen uptake (peak V 0 3 during maximal work does not appear to be hampered (7,30), even when wrestlers reduce their body weight by as much as 8%. Others have found that peak VOz and endurance time for running on the treadmill were decreased (77); these changes could be caused by rapid weight loss-induced decreases in muscle glycogen, plasma volume, and impaired thermoregulation.…”
supporting
confidence: 63%
“…This is true whether it was static strength that was measured, a s in earlier studies (1,58,61,73), or dynamic strength (30,80) and anaerobic"owera (34,48,52), as assessed in more recent research. FYgure 1 depicts the relationship between weight$loss and shortterm, high intensity performance from.previous~research~on wrestlers.…”
Section: Effects On Performancementioning
confidence: 98%
See 3 more Smart Citations